2021
DOI: 10.1001/jamanetworkopen.2021.25381
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Silicone Particle Migration Among Women Undergoing Removal or Revision of Silicone Breast Implants in the Netherlands

Abstract: Key Points Question Are cohesive gel breast implants associated with silicone bleed? Findings In this case series including 389 women with silicone gel breast implants, 384 women (98.8%) showed silicones in the tissues. There was no statistically significant difference between women with cohesive gel implants and those with noncohesive gel implants. Meaning These findings suggest that cohesive silicone gel breast implants leak si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
0
25
0
2
Order By: Relevance
“…Their contents were mixtures of various sized polymer compounds, many of which are smaller than the pores of the shell ( 6 ) and consequently bleeding occurrs ( 7 ). The latest generation of SBIs consists of a high cohesive gel but also in these latest types, gel bleed still occurs and will increase over time, due to biodegradation of the cohesive gel and the implant shell ( 8 – 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their contents were mixtures of various sized polymer compounds, many of which are smaller than the pores of the shell ( 6 ) and consequently bleeding occurrs ( 7 ). The latest generation of SBIs consists of a high cohesive gel but also in these latest types, gel bleed still occurs and will increase over time, due to biodegradation of the cohesive gel and the implant shell ( 8 – 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the newer generation of silicone gel implants degrade over time, with changes in color, clarity, and silicone cohesion [ 7 ]. These changes gradually increase the risk of silicone release following a rupture event, eventually resulting in no statistical difference in silicone leakage rates between the newer gel and older liquid silicone implants [ 7 , 8 ]. This may be an early indication that silicone leakage from breast implant rupture may not just be a problem of the past but an ongoing issue into the future.…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of exposure via all these sources is not known and was therefore not considered in this review. However, it is known that today, human exposure to siloxanes through the environment [38], by cosmetic products [39], and medical devices [40] far exceeds that due to the additive E900 from food intake.…”
Section: Biological and Toxicological Effects Of Pdmsmentioning
confidence: 99%